2019
DOI: 10.3390/info10040149
|View full text |Cite
|
Sign up to set email alerts
|

A Collaborative Pilot Platform for Data Annotation and Enrichment in Viticulture

Abstract: It took some time indeed, but the research evolution and transformations that occurred in the smart agriculture field over the recent years tend to constitute the latter as the main topic of interest in the so-called Internet of Things (IoT) domain. Undoubtedly, our era is characterized by the mass production of huge amounts of data, information and content deriving from many different sources, mostly IoT devices and sensors, but also from environmentalists, agronomists, winemakers, or plain farmers and intere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…The goal of these investments is to achieve productivity growth of at least 70% by 2050 [1] to meet the increased needs of the population of the Earth considering the fact that the area under cultivation will decrease. Emerging technologies such as Internet of Things (IoT) can provide significant potential in Precision Agriculture and Smart Farming, enabling the long-term increase in productivity [2]. The IoT (Internet of Things) paradigm offers a new perspective for precision agriculture enabling the real-time and site specific management of the cultivated fields.…”
Section: Introductionmentioning
confidence: 99%
“…The goal of these investments is to achieve productivity growth of at least 70% by 2050 [1] to meet the increased needs of the population of the Earth considering the fact that the area under cultivation will decrease. Emerging technologies such as Internet of Things (IoT) can provide significant potential in Precision Agriculture and Smart Farming, enabling the long-term increase in productivity [2]. The IoT (Internet of Things) paradigm offers a new perspective for precision agriculture enabling the real-time and site specific management of the cultivated fields.…”
Section: Introductionmentioning
confidence: 99%
“…Centralized architectures are also a main barrier towards scaling. Others suggested that explicitly accounting for weather-related power and internet outages in IoT platforms design lowers adoption barriers and prolongs deployment periods [64,65]. On the hardware side, battery capacity, lifetime and sensor storage capacity are among the challenges affecting adoption [59].…”
Section: Organizational Domain: Smart Agriculture and Farmingmentioning
confidence: 99%
“…that structure the unstructured data. Data annotation is one of the preprocessing techniques [5,6]. It is a process to label the data into its targeted classes [7,8].…”
Section: Introductionmentioning
confidence: 99%